Shape Co-Existence in the Transitional Nuclide 157 Yb - Xu Chuan; Hua Hui; Li Xiangqing; Zhang Shuangquan; Xu Furong; Shi Yue; Zhu Lihua; Wu Xiaoguang; Li Guangsheng; He Chuangye (Plasma Science and Technology, 2012)
High-spin states in 157 Yb have been populated in the 144 Sm( 16 O, 3n) 157 Yb fusion-evaporation reaction at a beam energy of 85 MeV, and two rotational bands have been established for the first time. Within the framework of the triaxial particle-rotor model, the energy spectra and single-particle configurations of 157 Yb are investigated. The calculated energy spectra agree well with the experimental data. The newly observed ν f 7/2 band, and the previously known ν i 13/2 band in 157 Yb, are also discussed by means of Total-Routhian-Surface methods. The structural characters observed in 157 Yb provide evidence for the shape coexistence of three distinct shapes: prolate, triaxial and oblate. At higher spins, both the ν f 7/2 band and the ν i 13/2 band in 157 Yb undergo a shape evolution with sizable alignments occurring.